BIRTH BY CESAREAN DELIVERY ON NEWBORN HEARING SCREENING TEST: A RETROSPECTIVE STUDY: Life Science - Medical - GOLJANIAN TABRIZI, ALI; ASADI, MAHBOOBE; BARATI, BEHROZ; SHAHABI RABORI, MARYAM (International Journal of Life Science and Pharma Research, 2017)
Hearing loss (HL) is the most common sensory disorder. False positive result of newborn hearing screening increases cost and maternal anxiety and worry. This retrospective observational study was performed in newborn hearing screening center between January 2013, and May 2015.All of the newborns with no risk factors were screened by otoacoustic emission test and timing and results of OAE and AABR tests were recorded.Overall, 1396 infants were studied. Results showed that there was no significant difference between OAE failure rates between two delivery mode groups after 3 day. Post ponding the first OAE after cesarean delivery should be considered to improve success rate, minimize maternal anxiety, and decrease costs.